(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
A microbiological evaluation of several environments of phytotherapics production (selection room (SS), stabilization stove (ES), and manipulation room (MP) were done Microorganisms and fungi were quantified, with plate count agar (PCA), potato dextrose agar (BDA) respectively, in presence of mint (Mentha sp), "guaco" (Mikania glomerata Sprengel), "poejo" (Mentha pulegium L.), lemongrass (Cymbopogum citratus (DC.) Stapf.) and chamomille (Matricaria chamomilla L.). Bigger contamination was verified on manipulation room in all cases, except with chamomille. There is a necessity to utilize disinfection methods to increase phytotherapics self-live.